Syncretism and the Negotiation of Cultural Memory: The Ritual Cleaning of Sacred Heirlooms in South Tangerang, Indonesia - Fariz Al Hazmi; Citra Aryandari; Yves P Cuenza (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2025)
This study examines the dynamics of syncretic negotiation of the heirloom-washing ritual practiced at Cilenggang, South Tangerang City, Indonesia. The ritual, maintained by the Cilenggang community since the 17th century, is associated with the legacy of Tubagus Muhamad Atif, an early disseminator of Islam in the region. Employing an ethnographic approach grounded in syncretism theory, this research explores how Islamic teachings and local cultural traditions are harmonized through ritual practice. Data were collected through observation, interviews, and literature review. The findings demonstrate that while traditional ritual media and equipment continue to reflect pre-Islamic cultural heritage, shifts in belief systems and ritual meanings indicate an ongoing negotiation shaped by Islamic influence. The incorporation of Islamic cultural expressions, such as hadroh music, da'wah activities, and Islamic dress codes, illustrates the adaptive and dialogic nature of the tradition. These findings highlight that syncretism is not a static condition but a continuous process of renegotiation shaped by social, religious, and cultural influences. This study contributes to a deeper understanding of syncretism as a mechanism through which local traditions are preserved, reinterpreted, and sustained within changing religious landscapes, offering broader insights into cultural resilience and community identity formation.